Emission Manipulation by DNA Origami‐Assisted Plasmonic Nanoantennas. Issue 21 (3rd August 2021) - Yeşilyurt, Ayşe Tuğça Mina; Huang, Jer‐Shing
Abstract: Plasmonic nanoantennas mediate far and near optical fields and confine the light to subwavelength dimensions. The spatial organization of nanoantenna elements is critical as it affects the interelement coupling and determines the resultant antenna mode. To couple quantum emitters to optical antennas, high precision on the order of a few nm with respect to the antenna is necessary. As an emerging nanofabrication technique, DNA origami has proven itself to be a robust nanobreadboard to obtain sub‐5 nm positioning precision for a diverse range of materials. Eliminating the need for expensive state‐of‐the‐art top‐down fabrication facilities, DNA origami enables cost‐efficient implementation of nanoscale architectures, including novel nanoantennas. The ability of DNA origami to deterministically position single quantum emitters into nanoscale hotspots further boosts the efficiency of light–matter interaction controlled via optical antennas. This review recapitulates the recent progress in plasmonic nanoantennas assisted by DNA origami and focuses on their various configurations. How those nanoantennas act on the emission and absorption properties of quantum emitters positioned in the hotspots is explicitly discussed. In the end, open challenges are outlined and future possibilities lying ahead are pointed out for this powerful triad of biotechnology, nanooptics, and photophysics. Abstract : DNA origami technology enables designable spatial arrangement of nanomaterials. This capability allows deterministically positioning single quantum emitters at the hotspots of plasmonic nanoantennas. When quantum emitters couple efficiently to plasmonic nanoantennas, their emission properties can be substantially modified, rendering DNA origami‐assisted plasmonic nanoantennas a promising platform for manipulating the emission of quantum emitters.